Значение православной духовности в процессе формирования гуманитарно-технической элиты - Скубченко, Сергий Протоиерей (НТУ "ХПИ", 2011)
The notion of “spirituality” was examined. The author focused on the attempts of abstracting of this notion and its shift into a purely material sphere. The sense of spirituality was described in a concrete religious meaning. The impossibility of the formation of humanitarian-technical elite without this important factor was highlighted.
Keywords: гуманитарно-техническая элита; православная духовность; деятельность человека